Reflexiones sobre los procesos de patrimonialización de los caminos antiguos en los Andes colombianos - Alejandro Bernal Vélez (Bulletin de l'Institut Français d'Études Andines)
This article is dedicated to the examination of pre-Hispanic and colonial roads situated within the Colombian Andes. It seeks to shed light on the diverse dynamics, ideas, values, actors, and institutions that are intricately intertwined with the processes involved in designating these roads as cultural patrimony. Commencing with an exploration of contemporary concepts pertinent to heritage-related matters, this article proceeds to delineate the treatment afforded to select regional cases of roads as objects of academic study and as objects that fall within the field of conservation and valuation heritage in Colombia. This article underlines the paucity of scholarly references pertaining to roads in this country’s archaeology. This deficiency, in turn, has far-reaching ramifications on the approaches adopted in the understanding of roads as heritage assets.